IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PENGUATAN PENDIDIKAN OLEH RESIMEN MAHASISWA SATUAN 126 MUHAWARMAN MELALUI CAGAR BUDAYA RADIO YBJ-6 PDRI - Adzikri, Fani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
This study aimed at describing the various strategies undertaken Student Regiment in implementing character education as a form of strengthening education through Radio Cultural Heritage YBJ-6 PDRI. This research was descriptive research using qualitative approach. This study was conducted at the Headquarters of the 126 Student Assembly Regiment of Muhawarman with commanders, staff and members. Data collection is done through observation, interview, and documentation. Technique examination of data validity used is triangulation technique. The results showed that the cultural heritage is an important thing that must be considered in the process of internalizing the value of character in the Student Regiment environment. Some strategies in implementing character education through cultural preservation such as the routine activities of state defending ceremonies, social service activities, and strengthening of national values. In the effort to implement character education can not be separated from the spirit of the commander, staff and members who synergize each other in creating a more positive unit.